Critério nas transferências voluntárias do governo do Estado do Ceará: político ou técnico? - Anchieta Júnior, Lourival (2013)
Since the republican regime has risen, the constitutional fiscal laws adopted in Brazil concentrate the administration of the main tributes in the states and federal government, which makes, therefore, the municipalities totally dependents on transfer funds from these governments, either constitutional or voluntaries. Aiming to contribute to the scientific literature, there is a need to further investigations on the characterization of the voluntary transfers, whose scenario in this work is the state of Ceará. This research presents an empirical study in an attempt to find out which criteria prevail in intergovernmental transfers from the State Government to the municipalities – either technical or political. Among the technical criteria chosen, we highlight the redistribution of wealth and management tool decentralization of public policy with the intention of improving social control, as well as reducing operating costs. The areas selected to represent such criteria were: wealth distribution, consumption, income and employment. In order to test the criteria transfers, political variables were chosen: the political identity between governor and mayor and the participation of the mayor’s political party in the coalition that contribute to the governor’s election. Due to data availability, a panel data was fit to a regression with fixed effects for Ceará municipalities in the period 2005–2009. Based upon reliable statistical estimates, it is concluded that political criteria that prevail in the decision to set the amount to be allocated to municipalities in Ceará through voluntary transfers.